Work-Life Imbalance: Its Impact on Employee Motivation and Well-Being - Hasyim Hasyim; Muhammad Bakri (Economics and Digital Business Review, 2025)
This study explores the complex relationship between work-life imbalance, employee motivation, and well-being. It aims to identify key causes, assess the multidimensional impacts on employees, and propose actionable strategies to mitigate the adverse effects of work-life imbalance in diverse organizational and cultural contexts. A systematic literature review (SLR) approach was employed to synthesize findings from recent studies on work-life imbalance. This qualitative analysis integrates theoretical perspectives, such as Boundary Theory and Self-Determination Theory, with empirical evidence to comprehensively understand the phenomenon. The study examines how organizational culture, technological demands, and industry-specific challenges contribute to the imbalance of work. The findings reveal that excessive workloads, technology-driven connectivity, and unsupportive organizational cultures contribute to work-life imbalance. This imbalance negatively affects employee motivation by eroding intrinsic drivers such as achievement and recognition and extrinsic factors like compensation and job security. Additionally, the study highlights significant psychological, emotional, physical, and social consequences, including stress, burnout, and deteriorating interpersonal relationships. These impacts vary across industries and cultural contexts, emphasizing the need for tailored organizational interventions. The study underscores the importance of implementing flexible work policies, mental health support programs, and inclusive workplace cultures to enhance employee well-being and organizational sustainability. These findings offer practical guidance for organizations balancing employee productivity with holistic well-being. The study also provides a foundation for future research on the long-term effects of interventions and emerging work trends.